IDENTIFIKASI TANAMAN OBAT DI LAHAN GAMBUT KECAMATAN PEDAMARAN KABUPATEN OGAN KOMERING ILIR - Ummi Hiras Habisukan (Bioilmi: Jurnal Pendidikan, 2021)
One of the characters that can be used as basic criteria for plant classification is morphological character. This study aims to determine the species used as medicine in peatlands, the parts of plants used, how to process and diseases that can be cured by medicinal plants in peatlands in Pedamaran District. This research is descriptive qualitative. The sampling technique is quota sampling and data analysis techniques are Miles and Huberman models. The results of identification research in Pedamaran District obtained nineteen species from nine families of medicinal plants and eight medicinal plants that have not been identified. The most widely used part is leaves, besides that there are also roots, stems, flowers, fruit, rhizomes, seeds, tubers and all parts. Based on this it can be seen that the plant can treat various diseases, including diabetes, hypertension, cholesterol, fever, diarrhea, itching on the skin caused by fungus such as phlegm and ringworm, vaginal discharge and nosebleeds, thrush, accelerate the process of wound healing and relieve menstrual pain. The most popular method of management is boiling. Another method is mashed and then smeared, ground and pasted, brewed and consumed directly.